Persepsi Masyarakat terhadap Fenomena Cancel Culture di Platform Digital - Nikmah Hadiati Salisah; Azha Putri Auwaly; Candy Aulia Putri Umu; Cindy Ayu Kusuma Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
In the digital era, social media has become a major public space where social, political, and cultural discourses thrive. One of the emerging phenomena is cancel culture, which is the collective practice of stopping support for individuals or groups due to actions that are considered problematic. This study aims to explore the perception of Indonesian society towards cancel culture on digital platforms using a qualitative approach. Data were obtained through literature studies, document analysis, and interviews with active users of social media such as Twitter, Instagram, and TikTok. The results of the study show that public perception is divided into two main poles: as a form of social responsibility and as digital persecution. The three main factors that influence this perception are social media as the main source of information, the individual's values ​​and social background, and emotional drives and FOMO. Cancel culture has a significant impact, both psychologically on the targeted individuals, and on society in the form of polarization and the loss of healthy discussion space. This study concludes that although cancel culture has the potential as a tool of social control, its practices need to be criticized so that they remain in line with the principles of justice and freedom of expression in digital democracy.